2004
DOI: 10.1002/mus.20046
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of quantitative motor unit action potential parameters

Abstract: We evaluated the test-retest reliability (reproducibility) of motor unit action potential (MUAP) parameters in multi-MUAP analysis over time. Reproducibility studies are not available for needle quantitative electromyography (QEMG) performed by the same examiner. Fourteen consecutive individuals (10 men and 4 women) had repeat QEMG at 3 hours after the first examination, and seven (5 men and 2 women) had a repeat QEMG after 4-10 days. The intraclass correlation coefficient (ICC) was 87-97% with same-day testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In the three repeated manual measurements, the mean durations ranged from 14.9 to 15.7 ms, and the largest difference between durations of MUAPs from the same MU was 8 ms [16]. Similar observations of such low degrees of reliability of manual duration readings have been reported by other authors [37][38][39].…”
Section: Variability Of Manual Measurementssupporting
confidence: 85%
“…In the three repeated manual measurements, the mean durations ranged from 14.9 to 15.7 ms, and the largest difference between durations of MUAPs from the same MU was 8 ms [16]. Similar observations of such low degrees of reliability of manual duration readings have been reported by other authors [37][38][39].…”
Section: Variability Of Manual Measurementssupporting
confidence: 85%
“…This might have been related to the high variability inherent in the MUP phase measures [21-23] or again due to a lack of statistical power resulting from the small sample size recruited, since there was a tendency for the severe CTS group to have more phases and turns in their MUP waveforms (Table 3). Other researchers have found low reliably in determining MUP onset and end markers as compared to the high reliability found in determining the peaks [19,21,24]. Calder et al [19] recently concluded that MUP duration (ICC: -0.29) and the number of phases in the MUP (ICC: -0.69) had poor within-subject reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Algorithms used to automatically measure MUP duration are based on amplitude and slope criteria, but because of variable amounts of background noise, the algorithms have low stability and visual inspection and manual marker adjustments are often required (Bischoff et al, 1994;Stalberg et al, 1995;Takehara et al, 2004b). Previous studies have shown low reliability in manual placement of duration markers and therefore manual corrections do not guarantee reliable estimates of MUP duration (Chu et al, 2003;Nandedkar et al, 1988;Rodriguez et al, 2007;Stalberg et al, 1986;Takehara et al, 2004a). In a study conducted by Rodriquez et al (Rodriguez et al, 2007) where the variability between two experienced electromyographers in manual measurements of MUP duration using four automated methods was examined, significant differences within electromyographers and between electromyographers were found in the tibialis anterior (TA) muscle but not in the FDI.…”
Section: Mup Durationmentioning
confidence: 94%